Principles of Lateral Craniofacial Reconstruction - Wang, Steven J.; Fung, Kevin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This text comprehensively reviews the major reconstruction challenges that are associated with the extirpation of tumors of the parotid gland and the lateral craniofacial region. It covers major functional and cosmetic consequences related to facial nerve paralysis, facial contour deformity, and soft tissue loss including the skin, ear, temporal bone, mandible, orbit, and cranial base. The text also includes basic concepts, a practical anatomical defect-based approach, and will highlight specific technical challenges that are commonly encountered in the contemporary era of intensive chemoradiation therapy, the aging population, and global health. Principles of Lateral Craniofacial Reconstruction will be a great resource for residents and fellows in training and practitioners in otolaryngology, plastic surgery, facial plastic surgery, oral maxillofacial surgery, ophthalmology, head and neck surgery, and oculoplastic surgery.
Section I: Basic Concepts and Principles -- Lateral Craniofacial Anatomy -- Anatomic Defect-based Approach to Reconstruction -- Section II: Defect Specific Reconstructive Issues -- Cutaneous Considerations in Lateral Craniofacial Reconstruction -- Soft Tissue Considerations in Lateral Craniofacial Reconstruction -- Maxillomandibular Considerations in Lateral Craniofacial Reconstruction -- Rehabilitation of Facial Palsy-The Brow -- Surgical Rehabilitation of Facial Paralysis-Eyelids and Lower Face -- Parotidectomy Defect and Facial Nerve Reconstruction -- Section III: Special Considerations -- Role of Prosthetics/osseointegration in Lateral Craniofacial Reconstruction -- Technical Issues in the High Risk Patient -- Lateral Craniofacial Reconstructive Challenges in the Developing World -- Emerging New Technologies.
Keywords: Otolaryngologic surgery; Plastic surgery; Head and Neck Surgery; Plastic Surgery